Color atlas and synopsis of cardiovascular MR and CT - Raman, Subha V. (McGraw-Hill Education Medical, 2014)
Color Atlas and Synopsis of Cardiovascular MR & CT does more than help you interpret cardiac and vascular CT and MR images. It also provides guidance on the diagnosis and management of patients undergoing those tests. Presented in a concise, easy-to-read design that is perfect for busy clinicians, the book features a comprehensive collection of more than 360 cardiac images and includes coverage of normal anatomy, radiographic anatomy, indications, contraindications, interpretations, and patient management.